Public Willingness to Pay for an Entrance Fee to National Elephant Conservation Center (NECC), Peninsular Malaysia - Juita Saleha Nordin; Nitanan Koshy Matthew; Chong Leong Puan (SAGE Open, 2023)
Wildlife especially large mammals such as elephants are an important part of an ecosystem providing various ecological functions and services, although they are often involved in human-wildlife conflict. The National Elephant Conservation Center (NECC) in the Pahang state of Peninsular Malaysia was established to ensure that the survival of the Asian Elephant ( Elephas maximus ) in Peninsular Malaysia through direct management, as well as educational and public awareness activities. However, no entrance fee has been imposed since the establishment of the center in 1989 (32 years). This study aimed to determine public willingness to pay for an entrance fee in the NECC. By using the open-ended contingent valuation method (CVM), the mean public willingness to pay for an entrance fee in the NECC during the non-peak season amounted to RM4.65/person/visit whereas it was RM7.09/person/visit during the peak season. The study would serve as a reference for entrance fee implementation for a conservation center as a form of financial aid to sustain the center as well as highlight the importance of public engagement in elephant conservation.